Sweetclover Production and Use in Florida - Carrol G. Chambliss (EDIS)
This document is SS-AGR-189, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2003.